2015
DOI: 10.1002/adhm.201500338
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Stiffness Modulates the Expression of Functional Proteins and Growth Factors in Endothelial Cells

Abstract: Angiogenesis, the formation of blood vessels from pre-existing ones, is of vital importance during the early stages of bone healing. Extracellular stiffness plays an important role in regulating endothelial cell behavior and angiogenesis, but how this mechanical cue affects proliferation kinetics, gene regulation, and the expression of proteins implicated in angiogenesis and bone regeneration remains unclear. Using collagen-coated polyacrylamide (PAAm) hydrogels, human umbilical vein endothelial cells (HUVECs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The increased levels of ASC proteins and mRNAs observed on stiff matrices suggest that there is a potential relationship between the Rho/ROCK and Wnt/β‐catenin pathways. Mechano‐chemical stimuli generated as a result of culture on stiff matrices leads to ASCs spreading and an increase in cell tension, which is known to initiate RhoA and ROCK and trigger the activation of β‐catenin (Samuel et al, ; Santos et al, ). In this study, the Wnt/β‐catenin pathway had a negative effect on adipogenic differentiation whereas other studies have shown that the epidermal Wnt/β‐catenin pathway is a potent initiator of adipogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…The increased levels of ASC proteins and mRNAs observed on stiff matrices suggest that there is a potential relationship between the Rho/ROCK and Wnt/β‐catenin pathways. Mechano‐chemical stimuli generated as a result of culture on stiff matrices leads to ASCs spreading and an increase in cell tension, which is known to initiate RhoA and ROCK and trigger the activation of β‐catenin (Samuel et al, ; Santos et al, ). In this study, the Wnt/β‐catenin pathway had a negative effect on adipogenic differentiation whereas other studies have shown that the epidermal Wnt/β‐catenin pathway is a potent initiator of adipogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that vascular organization is also dependent on the mechanical properties of the matrix in which the endothelial cells reside. A study by Santos et al demonstrates that HUVECs grown on collagen-coated polyacrylamide hydrogels of low (3 kPa) and high (30 kPa) stiffness display similar proliferation and gene transcription levels, but show a lower expression of the functional VEGF receptor-2 protein on the stiffer substrate [65], which means that the extent to which endothelial cells are responsive to angiogenetic processes depends on the mechanical environment. In a different study, Mason et al used a system where the stiffness of a collagen hydrogel can be changed without significant changes to the collagen density and architecture.…”
Section: Mechanobiologymentioning
confidence: 99%
“…Increased stiffness of polyacrylamide (PA) scaffolds from 1 to 10 kPa has been shown to boost the endothelial cell response to VEGF by increasing VEGFR-2 internalisation (LaValley et al, 2017). Similarly, increased stiffness of collagen coated PA gels in a range from 3 to 3,000 Pa affected the expression of functional proteins and GF in HUVECs, but did not affect their proliferation and gene expression (Santos et al, 2015). Differentiation of endothelial progenitor cells was proportional to the stiffness of the PDMS scaffolds (Xue et al, 2017).…”
Section: Mechanical Properties Of the Scaffoldmentioning
confidence: 99%